Comment on ‘Musculoskeletal Ultrasound Assessment of the Clinical Efficacy of the Combination of Acupressure and “Three Methods of Neck Movement (TCM)” Therapy in the Treatment of Cervical Spondylosis: A Study Protocol for a Randomized Controlled Trial’ [Response to Letter] - Zuo J; Zeng X; Ma H; Chen P; Cai X; Fan Z; Qu J (Journal of Pain Research)
Jinhong Zuo, Xiayang Zeng, Hongyi Ma, Peng Chen, Xinlei Cai, Zhenyu Fan, Jianpeng Qu Massage Department, Zhejiang Hospital, Hangzhou City, People’s Republic of ChinaCorrespondence: Jianpeng Qu, Massage Department, Zhejiang Hospital, No. 12 Lingyin Road, Xihu District, Hangzhou City, 310000, People’s Republic of China, Email qjp0007@126.com